HUBUNGAN KONDISI PSIKOSOSIAL DENGAN KEJADIAN DEPRESI POSTPARTUM DI WILAYAH KERJA PUSKESMAS KECAMATAN PASAR MINGGU - Rifda Hasanah Fauzi (2022)
Postpartum depression is a severe and general sadness with more unstable mood changes, serious and persistent symptoms. Psychosocial conditions are psychological and social conditions of the mother that can interfere with the mother's emotions and social life. Psychosocial conditions are one of the causes of postpartum depression. This study aims to determine the relationship between psychosocial condition and postpartum depression at the Pasar Minggu District Health Center. The research design used was cross sectional with 134 samples and the sampling technique used was purposive sampling. Data was collected through a questionnaire consisting of three parts, namely demographics, Postnatal Risk Questionnaire (PNRQ) to measure psychosocial conditions and Edinburgh Postpartum Depression Scale (EPDS) to measure postpartum depression. The results of the bivariate test with the chi-square test showed a significant relationship (p-value < 0,05) between psychosocial conditions and the incidence of postpartum depression (p-value = 0,008, OR = 0,34). For mothers who are identified as postpartum depression, they can consult their health to the mental poly at the Pasar Minggu District Health Center. Future research can continue research by adding variables or experimental studies related to interventions to prevent or reduce the occurrence of postpartum depression.